Molecular Mechanisms Underlying Synaptic and Axon Degeneration in Parkinson’s Disease - Gcwensa, Nolwazi Z.; Russell, Drèson L.; Cowell, Rita M.; Volpicelli-Daley, Laura A. (Frontiers in Cellular Neuroscience, 2021)
Parkinson’s Disease (PD) is a progressive neurodegenerative disease that impairs movement as well as causing multiple other symptoms such as autonomic dysfunction, rapid eye movement (REM) sleep behavior disorder, hyposmia, and cognitive changes. Loss of dopamine neurons in the substantia nigra pars compacta (SNc) and loss of dopamine terminals in the striatum contribute to characteristic motor features. Although therapies ease the symptoms of PD, there are no treatments to slow its progression. Accumulating evidence suggest that synaptic impairments and axonal degeneration precede neuronal cell body loss. Early synaptic changes may be a target to prevent disease onset and slow progression. Imaging of PD patients with radioligands, post-mortem pathologic studies in sporadic PD patients, and animal models of PD demonstrate abnormalities in presynaptic terminals as well as postsynaptic dendritic spines. Dopaminergic and excitatory synapses are substantially reduced in PD, and whether other neuronal subtypes show synaptic defects remains relatively unexplored. Genetic studies implicate several genes that play a role at the synapse, providing additional support for synaptic dysfunction in PD. In this review we 1) provide evidence for synaptic defects occurring in PD before neuron death, 2) describe the main genes implicated in PD that could contribute to synapse dysfunction, and 3) show correlations between the expression of Snca mRNA and mouse homologs of PD GWAS genes demonstrating selective enrichment of Snca and synaptic genes in dopaminergic, excitatory and cholinergic neurons. Altogether, these findings highlight the need for novel therapeutics targeting the synapse and suggest that future studies should explore the roles for PD-implicated genes across multiple neuron types and circuits.